Magnetomicelles: Efficient Cisplatin Pro‐Drug Delivery Visualized with Sub‐100 nm Resolution: Interfacing Engineered Thermosensitive Magnetomicelles With a Living System (Adv. Mater. Interfaces 7/2014). Issue 7 (October 2014) - Vitol, Elina A.; Rozhkova, Elena A.; Rose, Volker; Stripe, Benjamin D.; Young, Natalie R.; Cohen, Ezra E. W.; Leoni, Lara; Novosad, Valentyn
<x xml:space="preserve">Abstract</x> The Synchrotron X‐ray fluorescence micrograph shows the distribution of platinum within a single cancer cell. Pseudocolor images are created by correlating the concentrations with a color spectrum. In article 1400182, E. A. Rozhkova and co‐workers demonstrate the efficient delivery of a cisplatin pro‐drug to a biological system; this is achieved using hybrid thermosensitive magnetic nanomicelles. For the first time, the interface between an advanced material and a single cell is visualized with an unprecedented high spatial resolution of 30 nm using a hard X‐ray nanoprobe. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>